First demonstration of multi-MeV proton acceleration from a cryogenic hydrogen ribbon target. (5th March 2018) - Kraft, Stephan D; Obst, Lieselotte; Metzkes-Ng, Josefine; Schlenvoigt, Hans-Peter; Zeil, Karl; Michaux, Sylvain; Chatain, Denis; Perin, Jean-Paul; Chen, Sophia N; Fuchs, Julien; Gauthier, Maxence; Cowan, Thomas E; et al.
Abstract: We show efficient laser driven proton acceleration up to 14 MeV from a 62 μ m thick cryogenic hydrogen ribbon. Pulses of the short pulse laser ELFIE at LULI with a pulse length of ≈350 fs at an energy of 8 J per pulse are directed onto the target. The results are compared to proton spectra from metal and plastic foils with different thicknesses and show a similarly good performance both in maximum energy as well as in proton number. Thus, this target type is a promising candidate for experiments with high repetition rate laser systems.